PREVALENCE AND MOLECULAR CHARACTERISATION OF TRYPANOSOMES OF CATTLE IN OGUN AND KADUNA STATES, NIGERIA (2015)
African animal trypanosomosis is a complex infectious disease responsible for production losses in livestock herds. The severity of the disease has been associated with different species and strains of trypanosomes which have not been characterized molecularly in Nigeria. Many of the previous studies conducted in Nigeria were based on microscopy and serology. This study accessed the prevalence of trypanosomes in the forest (Ogun State) and Savannah (Kaduna State) zones, being major ecological belts of tsetse flies infestation in Nigeria and also carried out molecular characterization and phylogenetic analysis of identified trypanosomes. Blood samples were collected from the jugular veins of 411 cattle (129 males and 282 females), studied between May and October 2010 using systematic random sampling method. These included Muturu (112), N’dama (31), Sokoto Gudali (68) and White Fulani (200) breeds of ages 6 months to 3 years. Trypanosomes were detected by microscopy and species-specific Polymerase Chain Reaction (PCR) techniques. Sequencing of the ITS-1 region of ribosomal DNA gene were carried out for phylogenetic analysis using Molecular Evolutionary and Genetic Analysis software. Data were analyzed using descriptive statistics and Chi-square test at P = 0.05. The overall prevalence of trypanosomes in cattle were 15.1% and 63.7% for microscopy and PCR, respectively. By microscopy, T. brucei (3.6%), T. congolense (5.2%) and T. vivax (6.3%) were detected, while PCR detected T. congolense savannah (48.7%), T. congolense forest (0.5%), T. vivax (26.0%), T. brucei (4.4%) and T. evansi (0.5%). Prevalence by microscopy and PCR was significantly higher in Ogun State (18.1% and 75.1%) than in Kaduna State (8.9% and 35.6%). Trypanosoma congolense savannah and forest types were detected in Ogun State but only T. congolense savannah was detected in Kaduna State. The strains of T. brucei in Kaduna were different from those in Ogun State due to common nucleotide deletion points at loci 186, 279, 280, 281 and 325 of the sequences from Ogun State and nucleotide alterations from G ⇢ T, C ⇢ T and G ⇢ A at loci 124, 197 and 201, respectively. Sequence polymorphism of the ITS-1 region was highest in T. brucei brucei compared to T. congolense and T. vivax. Phylogenetic analysis revealed that T. vivax from cattle in Kaduna and Ogun States clustered together and had 100% and 96% homology to those detected in cattle in Venezuela and Zambia, respectively. However, T. brucei from Kaduna and Ogun States clustered into two separate clades and both had 98% and 95% homology respectively, to those detected in cattle in Zambia. This is the first report of the molecular characterization of T. congolense savannah and forest types in Nigeria. The genetic relatedness of trypanosomes from Nigeria to that of Venezuela and Zambia implies that the treatment regime known to be successful in the two countries can be adopted in Nigeria. It is recommended that regular surveillance and screening for new strains of trypanosomes be conducted on Nigerian cattle for effective prevention and control of the disease.